2003
DOI: 10.1034/j.1398-9995.2003.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of an early respiratory syncytial virus infection and atopic allergy

Abstract: An early RSV infection results in reduction of SPT positivity but not of occurrence of atopic diseases. This finding might explain why there is less atopic sensitization in countries with a greater probability of acquiring RSV infection at an early age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
5
43
0
1
Order By: Relevance
“…56 -58 Two other articles did not show an association between RSV infection and physician-diagnosed asthma 52,53 : Juntti did not find an association, although in children with asthma the disease appeared significantly sooner in those who had a history of RSV. 52 Finally, Korppi followed-up children with RSV infection and a control group for 20 years, and found that RSV was a risk factor for altered pulmonary function independent of atopia. He concluded that RSV bronchiolitis was not a predisposing factor for the development of asthma and atopia, although it might be a marker for immunologic changes that are common to both disorders.…”
Section: Resultsmentioning
confidence: 98%
“…56 -58 Two other articles did not show an association between RSV infection and physician-diagnosed asthma 52,53 : Juntti did not find an association, although in children with asthma the disease appeared significantly sooner in those who had a history of RSV. 52 Finally, Korppi followed-up children with RSV infection and a control group for 20 years, and found that RSV was a risk factor for altered pulmonary function independent of atopia. He concluded that RSV bronchiolitis was not a predisposing factor for the development of asthma and atopia, although it might be a marker for immunologic changes that are common to both disorders.…”
Section: Resultsmentioning
confidence: 98%
“…An early case control study from the US showed an increased risk of bronchiolitis in families with C1 smoker (McConnochie and Roghmann 1960) but several other prospective case-control studies showed a significant effect in univariate analysis (P = 0.018 and 0.0004, respectively) but not in multivariate analysis (Bulkow et al 2002;Sigurs et al 1995;Juntti et al 2003). A large cohort study in Arizona showed no significant effect of environmental tobacco smoke exposure in a multivariate analysis (Holberg et al 1991) while a more recent large nested casecontrol study from the Danish birth cohort (2564 infants and children hospitalized with RSV and 12816 age-matched controls) (Stensballe et al 2006), found an association between tobacco smoke exposure and an increased risk of hospitalization with RSV (odds ratio: 1.35; 95 % confidence interval: 1.20-1.52).…”
Section: Risk Factors For Infection and Diseasementioning
confidence: 96%
“…RSV is implicated in asthma and allergy, although reports are conflicting with some suggesting that prior RSV infection protects against development of atopy as determined by skin prick test [41] and others suggesting that RSV infection predisposes to the development of allergic conditions such as asthma [42,43]. Serum collected from RSV-infected patients contains elevated Th2 cytokines and IgE [44,45], suggesting that viral infection induces an allergy-like condition.…”
Section: Discussionmentioning
confidence: 99%